Effectiveness of Counseling in Schools: a study with reference to Emotional Maturity among Adolescents. - Paul, Cinu I. (Journal of Social Work Education and Practice, 2017)
Children and adolescents are considered as the valuable asset of any country. Such an emphasis is obviously based on the immense potentials of the youth persons to contribute intellectually, politically and economically to the society. They need to be well adjusted to their physical, intellectual, emotional, social and spiritual competences need to be properly developed. This is achieved through family, school community and society. Among all these agencies, the school system and the teachers play a vital role in molding healthy personalities. If a favorable environment is produced in schools, it would go a long way in promoting the mental health of children and adolescents, preventing several emotional problems, and offering timely intervention for their psychological problems through appropriate psycho social care by school counselors. The study is a modest attempt to examine the effectiveness of counseling services offered to the students and the difference it creates in certain domains of their personality. The research design is descriptive in nature and the sampling technique adopted for the study is stratified random sampling. From the findings it was concluded that, even though the emotional maturity level increases after a good counseling, it was observed that the results among adolescent boys showed a sheer decline in emotional maturity after their counseling. This shows some revamp in counseling models as such.